2012
DOI: 10.1371/journal.pone.0052312
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein Levels in Blood Plasma from LRRK2 Mutation Carriers

Abstract: The diagnosis of Parkinson’s disease (PD) remains primarily a clinical issue, based mainly on phenotypic patterns. The identification of biomarkers capable of permitting the preclinical detection of PD is critically needed. α-Synuclein is a key protein in PD, with missense and multiplication mutations in the gene encoding α-synuclein (SNCA) having been reported in familial cases of PD, and accumulation of the protein identified in Lewy bodies (LBs) and Lewy neurites (LNs) in affected brain regions. With the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 44 publications
4
36
0
3
Order By: Relevance
“…Early studies seeking to establish a correlation between PD and ␣-syn levels in human CSF using ELISA-based methods suggested that PD patients could be characterized by a lower total ␣-syn CSF level (25)(26)(27)(28)(29)(30)(31); similar findings were recently reported for blood plasma (32). Other groups have quantified CSF ␣-syn using "quasi-solution," bead-based Luminex® xMAP immunoassays, which are reportedly more sensitive than conventional ELISAs (33) and also reported lower total ␣-syn in PD patients than in healthy individuals (34,35).…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Early studies seeking to establish a correlation between PD and ␣-syn levels in human CSF using ELISA-based methods suggested that PD patients could be characterized by a lower total ␣-syn CSF level (25)(26)(27)(28)(29)(30)(31); similar findings were recently reported for blood plasma (32). Other groups have quantified CSF ␣-syn using "quasi-solution," bead-based Luminex® xMAP immunoassays, which are reportedly more sensitive than conventional ELISAs (33) and also reported lower total ␣-syn in PD patients than in healthy individuals (34,35).…”
supporting
confidence: 67%
“…Using such assays, elevated levels of ␣-syn oligomers have been detected in the CSF of PD patients (28,43). However, such a difference was not observed when analyzing ␣-syn oligomers in blood plasma (32).…”
mentioning
confidence: 99%
“…Among biochemical biomarkers, α‐syn has been extensively studied as a candidate biomarker for PD in biological fluids especially in serum, plasma, and cerebrospinal fluid (CSF) (Gorostidi et al . ; Aasly et al . ; Kasai et al .…”
Section: α‐Synuclein As a Target For Diagnosismentioning
confidence: 98%
“…Among biochemical biomarkers, a-syn has been extensively studied as a candidate biomarker for PD in biological fluids especially in serum, plasma, and cerebrospinal fluid (CSF) (Gorostidi et al 2012;Aasly et al 2014;Kasai et al 2014;Landeck et al 2016;Simonsen et al 2016;Majbour et al 2017;Mollenhauer et al 2017). Some studies have reported decreased levels of total a-syn (t-a-syn) in CSF from patients with PD compared to control (Tokuda et al 2006;Mollenhauer et al 2008Mollenhauer et al , 2011Hong et al 2010;Parnetti et al 2011).…”
Section: A-synuclein As a Target For Diagnosismentioning
confidence: 99%
“…Compared to healthy controls, Gorostidi and colleagues found a significant decrease in plasma total α-synuclein levels in idiopathic PD patients and the reduction was less significant in patients who were LRRK2 mutation carriers [20]. However, Foulds and colleagues had a substantially different conclusion: there were no differences in the plasma total α-synuclein levels between PD patients and controls, which may be due to large individual-to-individual variation [21].…”
Section: Abnormal Protein Accumulation and Aggregation α-Synucleinmentioning
confidence: 97%